Economic questions of maize production on different soil types - Sulyok, Dénes (Acta Agraria Debreceniensis, 2012)
The requirements and objective of cultivation are in constant change. For example, different cultivation systems are developed for the purpose of soil protection, the preservation of its moisture content and on soils with various precipitation supply or production site conditions. Traditionally, one of the most important cultivation aims is crop needs. Further cost saving in fertilisation and crop protection can only be achieved by reducing the quality and quantity of production or it cannot be achieved at all. Furthermore, the costs can be significantly reduced by means of the rationalisation of cultivation. Energy and working time demand can also be notably reduced if ploughing is left out from the conventional tillage method. The key requirement of economicalness is to perform the cultivation at the optimal date, moisture level and the lowest possible cost. Within production costs, the cost of cultivation is between 3–17%, while they are between 8–36% within machinery costs. It is the vital condition the usability of each technological method to progressively reduce costs. Our evaluation work was carried out with the consideration of the yield data obtained from cooperating farms and the experiment database of the Institute for Land Utilisation, Regional Development and Technology of the Centre for Agricultural and Applied Economic Sciences of the University of Debrecen. Three technological methods (ploughing, heavy cultivator and loosening tillage) were used on several soil types which differ from in terms of cultivability (chernozem, sandy and sandy clay soils) from the economic/economical aspect. We examined the sectoral cost/income relation of maize production as an indicator plant. The maize price during the analytical period was 45 thousand HUF per t. On chernozem soils, the production of maize can be carried out on high income level, while maize production on sandy soils has a huge risk factor. The role of cultivation is the highest on high plasicity soils, since they have a huge energy demand and the there is a short amount of time available for each procedure in most cases.